Sessizliğin sesi (İstanbul İstanbul İstanbul İstanbul İstanbul)
6 cilt (1. c. [3], 159 sayfa ; 2. c. [3], 201 sayfa, [1] s. resim ; 3. c. [3], 150 sayfa ; 4. c. 133 sayfa ; 5. c. 157 sayfa ; 6. c. 187, [2] sayfa)